Methodological guide: Community participatory inventory and prioritization of climate-smart crop-livestock agroforestry technologies / practices - Bayala, Jules; Ayantunde, Augustine A.; Somda, Jacques; Ky-Dembélé, Catherine; Bationo, B. André; Sanogo, Diaminatou; Tougiani, Abasse; Zougmoré, Robert B. (2018)
This guide addresses the issue of identifying priority interventions for communities in the face of climate change. The manual is about participatory approach of inventorizing and prioritizing climate-smart crop-livestock-agroforestry and social technologies / practices. The guide provides a step by step guidance on how project/extension workers can work with communities and other development stakeholders in the target sites to identify practices that can help local communities to better adapt to climate variability in production. The guide was developed within the framework of a project “Building resilient agro-sylvo-pastoral systems in West Africa through participatory action research” (BRAS-PAR)” which is one ofthe flagship 2 projects funded by the CGIAR Research Program on Climate Change Agriculture and Food Security (CCAFS). The flagship 2 of CCAFS, which is about climate-smart technologies and practices, addresses the challenge of how to transition to a climate-smart agriculture (CSA) at a large scale for enabling agricultural systems to be transformed and reoriented to support food security under the new realities of climate change. Led by ICRAF-WCA/Sahel, the BRAS-PAR project is being implemented by a consortium of National research institutes in Burkina Faso, Ghana, Niger and Senegal, IUCN, and ILRI.